2015
DOI: 10.1093/intimm/dxv034
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory B cells in anti-tumor immunity

Abstract: Advances in understanding of the immune microenvironment have highlighted the role of immunosuppressive T cell, myeloid, dendritic and monocytic sub-populations in inhibition of the anti-tumor immune response. The role of B cells in modulating the immune response to solid tumors as well as lymphoid malignancies is less well understood. Murine models of autoimmune disease have defined B regulatory cell (Breg) subsets with immune suppressive activity, including B cell subsets that express IL-10, and transforming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 108 publications
1
81
0
3
Order By: Relevance
“…To treat diseases such as RA, it is crucial that the Bregs migrate to the inflamed joints. While there is some evidence from murine studies showing that Bregs migrate to sites of inflammation (65), this requires further evaluation. It must be noted that while in vitro culture studies provide an indication of Breg function in vivo, they are not truly representative of Bregs at the site of inflammation.…”
Section: Challenges and Outstanding Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To treat diseases such as RA, it is crucial that the Bregs migrate to the inflamed joints. While there is some evidence from murine studies showing that Bregs migrate to sites of inflammation (65), this requires further evaluation. It must be noted that while in vitro culture studies provide an indication of Breg function in vivo, they are not truly representative of Bregs at the site of inflammation.…”
Section: Challenges and Outstanding Questionsmentioning
confidence: 99%
“…More recently, it has been suggested that tumor-infiltrated B cells develop immune-suppressive properties via enhanced expression of TGF-β, PD-L1, CD86, and IL-10 (65). In this model, tumor-infiltrating B cells that were not initially intrinsically suppressive developed a Breg phenotype upon exposure to the tumor microenvironment (65). Some of the identified factors promoting a Breg phenotype are tumor-derived metabolites of 5-lipoxygenase in a breast cancer model, and placental growth factor (PIGF) in gliomas (66,67).…”
Section: Role In Diseasementioning
confidence: 99%
“…Interestingly, depleting B cells with anti-CD20 monoclonal antibody (mAb) alone does not inhibit tumor progression, but improves response in combination with chemotherapy ( 5 ). One suggested mechanism for TIL-B enhancement of tumor progression is through a subset of B cells that are suppressive, thereby inhibiting the antitumor immune responses ( 6 ). Similarly, in a transgenic metastatic, castration-resistant prostate cancer model ( 7 ), progression of the disease is associated with immune infi ltrates, including B cells, which are recruited to the tumor by the chemokine CXCL13.…”
mentioning
confidence: 99%
“…Longtemps négligé, le rôle des LB (lymphocytes B) reste débattu. Si leur présence dans le microenvironnement tumoral est associée à un meilleur pronostic dans de nombreux cancers, elle peut aussi favoriser la progression tumorale [2,3]. Trois articles publiés en 2016 dans la revue Cancer Discovery décrivent le rôle protumoral des LB dans le cancer du pancréas le plus répandu, l'adé-nocarcinome canalaire pancréatique ou PDAC (pancreatic ductal adenocarcinoma), qui touche les cellules épithéliales des canaux pancréatiques ( Figure 1).…”
Section: Liens D'intérêtunclassified